Verbal art in translation: A Hasanian perspective on The River Merchant's Wife: A Letter. (September 2021) - Yu, Hailing
Abstract: Against the background of Systemic Functional Linguistics (SFL), Ruqaiya Hasan proposes a theory of verbal art, which extends the basic SFL model in search for a higher form of organization that bestows artistry to the literary text which is called a 'verbal art'. According to her theory, literary texts take advantage of both the semiotic system of language (a first-order semiosis) and the semiotic system of verbal art (a second-order semiosis). This study proposes that the theory can be applied to verbal art translation and resolve controversy over the quality of a translated literary work. The case study is Ezra Pound's The River Merchant's Wife: A Letter, translated from Changgan Xing by the ancient Chinese poet Li Bai. While praised by some for its poetic beauty, Pound's translation is criticized by others for containing 'errors'. The analysis from a Hasanian perspective demonstrates that both evaluations are justifiable. Inaccuracies in the first-order semiosis lead to the criticism of error, and successful re-creation of artistry in the second-order semiosis makes the translation a work of art in its own right. Recognition of the second-order semiosis of a verbal art will be helpful for literary translators and translation scholars. Highlights: Investigates Hasan's theory of verbal art which extends the basic SFL model for a higher form of organization in literary texts. Discusses the applicability of Hasan's framework to studies of verbal art translation. Demonstrates that Hasan's framework can help resolve controversy over the quality of Ezra Pound's translation. Calls for attention to the second-order semiosis of verbal art, wherein lies the challenge and artistry of translation.